Italic resonances in De lobos y del águila (Iter, 2022)
Ximena Godoy Arcaya ’s Fromwolvesand from the eagle, presents lyrics themes or motifs from the italianpoetry. The trip subject, the characters of Saint Francisco and SaintCecilia, the presence of the Donna and the Erosy the image of the wolfand the descent to the underworld are among them. The tone, lyric imagesythe semantic concentration and liguistic softeness abridge fromthe text a highly aesthetic poetic nucleus.